The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1982-0224-20130218
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Serrapinnus Malabarba, 1998 (Characidae: Cheirodontinae) from Rio Grande do Norte State, northeastern Brazil

Abstract: Serrapinnus potiguar, new species, is described from the rio Ceará-Mirim, a coastal drainage in the Rio Grande do Norte State, northeastern Brazil. The new species is distinguished from the other species of the genus by the shape and arrangement of the ventral procurrent caudal-fin rays of the sexually dimorphic males; where the hypertrophied elements present the shape of a series of scimitars arranged radially, forming a semi-circle on the ventral margin of the caudal peduncle. Furthermore, the new species is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 845 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…This ecoregion includes coastal basins located between São Francisco and Parnaíba river basins, draining Alagoas, Pernambuco, Paraíba, Rio Grande do Norte, Ceará, and a small portion of Piauí States (Rosa et al 2003). Albert et al (2011) listed 88 freshwater fish species from MNCE; however, new species are being found and described (e. g. Parotocinclus seridoensis Ramos, Barro-Neto, Britski & Lima, 2013; Serrapinnus potiguar Jerep & Malabarba, 2014;and Hypsolebias martinsi Britzke, Nielsen & Oliveira, 2016). The estimative of freshwater fish species number at Brazilian Northeast may be premature, given the lack of taxonomic revisions and few representative regional collections (Rosa et al 2003;Langeani et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…This ecoregion includes coastal basins located between São Francisco and Parnaíba river basins, draining Alagoas, Pernambuco, Paraíba, Rio Grande do Norte, Ceará, and a small portion of Piauí States (Rosa et al 2003). Albert et al (2011) listed 88 freshwater fish species from MNCE; however, new species are being found and described (e. g. Parotocinclus seridoensis Ramos, Barro-Neto, Britski & Lima, 2013; Serrapinnus potiguar Jerep & Malabarba, 2014;and Hypsolebias martinsi Britzke, Nielsen & Oliveira, 2016). The estimative of freshwater fish species number at Brazilian Northeast may be premature, given the lack of taxonomic revisions and few representative regional collections (Rosa et al 2003;Langeani et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…2) and S. potiguar (Jerep & Malabarba, 2014: fig. 2) are unique among cheirodontines and putatively a synapomorphy of those species.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis was discussed by Jerep & Malabarba (2014). These later authors noted that almost all morphological evidences of relationships among cheirodontine taxa were ignored by Mariguela et al (2013) in their discussion, and a few morphological characters reported in that study were chosen to support their phylogeny in that they corroborate their cladogram.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Costa, ; Costa & Vono, ; Fowler, ; Gurgel‐Lourenço et al . , ; Jerep & Malabarba, ; Novaes et al . , ; Ramos et al .…”
Section: Methodsunclassified
“…splink.org.br), NEODAT II (www.mnrj.ufrj.br/search1p.htm) and Global Biodiversity Information Facility (GBIF; gbif.org). Specialized taxonomic literature was also consulted (Britzke et al, 2016;Buckup et al, 2007;Costa, 2008;Costa & Vono, 2009;Fowler, 1941;Gurgel-Lourenço et al, 2013;Jerep & Malabarba, 2014;Novaes et al, 2013;Ramos et al, 2005Ramos et al, , 2013Reis et al, 2003;Rosa & Groth, 2004;Zawadzki et al, 2017) along with systematic compilations of MNCE freshwater fishes (Costa et al, 2017a(Costa et al, , 2017bLima et al, 2017;Nascimento et al, 2014;Paiva et al, 2014;Rodrigues-Filho et al, 2016;Rosa et al, 2003;Silva et al, 2014Silva et al, , 2017.…”
Section: Species Records and Taxonomic Validationmentioning
confidence: 99%